ANALISIS KESALAHAN EJAAN PADA BERITA POLITIK EDISI APRIL 2023 DALAM MEDIA MASSA DARING (DETIK.COM) - Khaerul Anwar; Samsul Bahri; Nana Triana Winata (Bahtera Indonesia, 2023)
This study analyzes and describes spelling errors in political news in the April 2023 edition of the Detik.com newspaper. The data in this study are spelling errors in the form of capital letters errors, word writing errors, italics errors, symbol writing errors. numbers, and punctuation errors. The objectives of this research include, among others, (1) knowing the types of spelling errors that exist in political news in the April 2023 edition of the Detik.com mass media and (2) analyzing and describing the forms of errors in the April 2023 edition of the Detik.com mass media. This research is a descriptive qualitative research with the subject of finding, analyzing, and describing data in the form of spelling errors. According to (Sugiyono, 2022) says that, "The qualitative research method is a research method based on the philosophy of postpositivism, used to research the conditions of natural objects, (as opposed to experiments) where the researcher is a key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive or qualitative, and the results of qualitative research emphasize meaning rather than generalization. The results of this study are as follows. (1) Errors in writing capital letters with lots of data, ten errors in writing capital letters, (2) Errors in writing words with lots of error marks, totaling twelve errors, (3) Errors in writing italics with a total of twenty-two errors, (4 ) Errors in writing number symbols with lots of data errors, namely four writing errors, and (5) Errors writing punctuation marks with lots of data errors totaling nine writing errors.